2021
DOI: 10.4103/tcmj.tcmj_168_20
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and diets – A review

Abstract: Stroke was one of the most common causes of death and disability worldwide. In addition, there was a significant increase in the disease burden of stroke in the world over the past 25 years, especially in developing countries. We searched PubMed (National Library of Medicine, USA) and Embase (Elsevier) databases using “Stroke and diets” as strategy, and additional references were obtained from the selected articles. The risk factors of stroke include age, sex, and modifiable factors such as hypertension, smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Although the burden of stroke has declined during the past few decades, stroke remains an important health problem in the world ( 2 , 3 ). The cost of stroke care brings a high burden on both society and patients’ families ( 13 ), and the first primary prevention of stroke is the most effective way to reduce the burden ( 9 ). Lead is an important environmental pollutant, and lead exposure caused nearly 5% of the total number of stroke deaths and DALYs in 2019 ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the burden of stroke has declined during the past few decades, stroke remains an important health problem in the world ( 2 , 3 ). The cost of stroke care brings a high burden on both society and patients’ families ( 13 ), and the first primary prevention of stroke is the most effective way to reduce the burden ( 9 ). Lead is an important environmental pollutant, and lead exposure caused nearly 5% of the total number of stroke deaths and DALYs in 2019 ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the cumulative effect of lead exposure, it may adversely affect multiple body systems, including respiratory, nervous, cardiovascular digestive, and kidney systems (10). Previous evidence has proved that lead exposure is an important risk factor for cardiovascular disease (including stroke) (9,(11)(12)(13)(14)(15)(16), and the National Health and Nutrition Examination Survey cohort study in the US found a dose-response relationship between blood lead level and stroke mortality (17). Moreover, another study found that, from 1990 to 2014, about 34,000-99,000 deaths have been avoided due to the decline in blood lead levels (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers find that foods associated with improved health also have low environmental impacts [2]. Increased meat consumption is found to be linked to the growth of degenerative disease (e.g., Alzheimer disease) [6], cancer [7,8], and stroke [9]. A more balanced and sustainable diet therefore will not only improve the quality of life and reduce national health care costs but also significantly lower the environmental impact of food consumption [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This study will investigate the impact of social influence on the consumption of meat and non-meat diets. We will focus on meat consumption partly because interest in nonmeat diets has been growing rapidly across the world in recent years, and also because there is a wide consensus now that increased meat consumption is linked to higher health risks [2,[6][7][8][9] and substantial environmental damage [44][45][46]. Using data from the 2014 British Social Attitude (BSA) Survey [47] and through the construction of an agent-based model, this study will enhance our understanding of the impact of social interactions and peer influence on the dynamics of the spread of various meat-eating behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…It is with great interest that we read the recently published review entitled “Stroke and Diets” in the Tzu Chi Medical Journal [ 1 ]. The authors provide a concise and up-to-date discussion on the role of different dietary patterns in the prevention of stroke.…”
mentioning
confidence: 99%